1997
DOI: 10.1172/jci119760
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQB1 polymorphism determines incidence, onset, and severity of collagen-induced arthritis in transgenic mice. Implications in human rheumatoid arthritis.

Abstract: Certain HLA-DR alleles have been associated with predisposition to human rheumatoid arthritis (RA). There is also evidence that certain HLA-DQ alleles may also be important in determining susceptibility to RA. We have previously demonstrated that mice transgenic for HLA-DQ8, a DQ allele associated with susceptibility to RA, develop severe arthritis after type II collagen immunization. To investigate the influence of polymorphic difference at the DQ loci on susceptibility to arthritis, we generated mice transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 64 publications
(37 reference statements)
1
53
1
1
Order By: Relevance
“…The enhancing DRB1 alleles are DRB1*0401 and *0404, whereas DRB1 alleles such as DRB1*0402, *1301, and 1302, which all encode the amino acid sequence motif 70 DERAA 74 in the HV3 region of the protein, are dominantly protective (6). Consistent with this model, DQ8 transgenic mice, but not DQ6 (DQB1*0601/DQA1*0103) transgenic mice, develop collagen-induced arthritis (7). The DQ3-DR4 haplotypes have a stronger association with RA and predispose to a more severe disease than the DQ5-DR1 and DQ5-DR10 haplotypes (8,9).…”
Section: P Redisposition To Rheumatoid Arthritis (Ra)mentioning
confidence: 81%
“…The enhancing DRB1 alleles are DRB1*0401 and *0404, whereas DRB1 alleles such as DRB1*0402, *1301, and 1302, which all encode the amino acid sequence motif 70 DERAA 74 in the HV3 region of the protein, are dominantly protective (6). Consistent with this model, DQ8 transgenic mice, but not DQ6 (DQB1*0601/DQA1*0103) transgenic mice, develop collagen-induced arthritis (7). The DQ3-DR4 haplotypes have a stronger association with RA and predispose to a more severe disease than the DQ5-DR1 and DQ5-DR10 haplotypes (8,9).…”
Section: P Redisposition To Rheumatoid Arthritis (Ra)mentioning
confidence: 81%
“…In contrast, transfection with a non-RA-associated gene, HLA-DQ6, created a phenotype resistant to the development of inflammatory arthritis. [18][19][20][21][22] Some association studies in humans have suggested a direct role for DQ alleles in RA. 23 However, further larger studies have not supported this hypothesis.…”
Section: -11mentioning
confidence: 99%
“…Transgenic mice expressing human class II molecules (in the absence of endogenous mouse class II) have been used to study other autoimmune disorders, including rheumatoid arthritis and multiple sclerosis (15)(16)(17)(18). We have studied the effect of gluten in double transgenic mice expressing HLA-DQ and human CD4 genes in the absence of endogenous class II and CD4 genes.…”
Section: Hla-dq Determines the Response To Exogenous Wheatmentioning
confidence: 99%